1986
DOI: 10.1111/j.1476-5381.1986.tb14580.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of selective 5‐hydroxytryptamine uptake inhibitors on 5‐methoxy‐N,N‐dimethyltryptamine‐induced ejaculation in the rat

Abstract: 1The ejaculatory response and the 5-hydroxytryptamine (5-HT) behavioural syndrome induced by 5-methoxy-N,N-dimethyltryptamine (5-MeODMT) (3 mg kg-' i.p.) were studied following acute and repeated treatment of rats with the selective uptake inhibitors of 5-HT, fluoxetine, zimeldine, alaproclate, and citalopram. The oral doses used were based on the respective EDM values for uptake inhibition. 2 Acute doses of fluoxetine and zimeldine significantly reduced the ejaculatory response when given 48 h before 5-MeODMT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…These authors postulated that 5-HT was acting on autoreceptors to inhibit their firing and release of 5-HT from projection sites. In contrast, augmentation of 5-HT activity also elicits spontaneous erections and ejaculatory responses (Berendsen and Broekktamp 1987;Renyi 1986). Therefore, 5-HT may have both facititatory and inhibitory effects on sexual function depending on the receptor subtype, location of receptors and the animal model.…”
Section: Discussionmentioning
confidence: 96%
“…These authors postulated that 5-HT was acting on autoreceptors to inhibit their firing and release of 5-HT from projection sites. In contrast, augmentation of 5-HT activity also elicits spontaneous erections and ejaculatory responses (Berendsen and Broekktamp 1987;Renyi 1986). Therefore, 5-HT may have both facititatory and inhibitory effects on sexual function depending on the receptor subtype, location of receptors and the animal model.…”
Section: Discussionmentioning
confidence: 96%
“…Pretreatment with the 5-HT synthesis inhibitor p-chlorophenylalanine or 5-HT 1/2 and 5-HT 2 receptor antagonists (methysergide, ritanserin and ketanserin) significantly abolished the ejaculatory response induced by PCA or fenfluramine (26,32,33). In addition, it has been shown that 5-HT 2 receptor agonist 5-methoxydimethyltryptamine facilitates ex copula seminal emission and ejaculation (20,27,28). 5-HT 2 receptors can be divided into three subtypes: 5-HT 2A , 5-HT 2B and 5-HT 2C receptors (11).…”
Section: Drugs and Treatmentsmentioning
confidence: 99%
“…This finding is consistent with identification of all three 5-HT, binding sites on spinal cord synaptosomes [Zemlan et al, 19901. In the cat, electrical stimulation of 5-HT-containing neurons in the caudal raphe nucleus, which sends projections to autonomic centers in the sacral spinal cord, inhibits bladder contractions [McMahon and Spillane, 19821. Furthermore, 5-HT agonists that effect the re-uptake or degradation of this monoamine transmitter to promote or inhibit various aspects of sexual behavior in the rat [Berendsen et al, 1990;Bitran and Hull, 1987;Lee et al, 1990;Mas et al, 1987;Renyi, 1986;Steers and de Groat, 1989;Szele et al, 19881. In humans the antidepressant trazodone, whose major metabolic product is the 5-HTIc,, agonist mchlorophenylpiperazine (mCPP), is useful in treating impotence [Adaikin et al, 19911. Likewise, tricyclic antidepressants whose pharmacological actions include blockade of 5-HT uptake are used to manage bladder hyperactivity and pain [Wein et al, 19911.…”
Section: Introductionmentioning
confidence: 99%